Role of ixodid ticks in tick-borne pathogen spread and circulation in the Belarusian Lakeland - A. A. Osmolovsky; I. A. Subotsina (Ветеринария сегодня)
Results of ixodid tick analysis for their ecological, epizootological and epidemiological significance for tick-borne pathogen spread across the Belarusian Lakeland are presented. The ticks were collected in publicly accessible areas of the Vitebsk Raion in April – November 2022: 8 routes were tracked, 18 flag-km were passed, 529 tick specimens were collected, including 350 imago ticks and 179 nymph ticks. The ixodid tick genus and species were determined using N. A. Filippova’s ixodid tick determinator. All caught ticks were tested for Borrelia spp., Anaplasma spp. (Ehrlichia spp.), Babesia spp. and Tick-borne encephalitis virus genetic materials with real-time polymerase chain reaction using the reagent kit for nucleic acid extraction from environmental samples in accordance with the manufacturer’s instructions. The specimens were grouped in accordance with the MG 3.1.1027-01 “Collection, recording and preparation for laboratory tests of blood-sucking arthropods being vectors of natural focal infections”; therewith, one specimen includes only one tick. Differences in the numbers of ixodid ticks and the occurrence of genetic markers of tick-borne pathogens in them were found to be associated with ecological characteristics of the examined territories. The following epidemically and epizootically significant ticks contributing to transmissible infection and invasion spread were found in the Belarusian Lakeland: ticks of Ixodes and Dermacentor genera; their frequency index was 70.1 and 29.9%, respectively. Tick-transmitted pathogen prevalence rate in the examined territories of the Vitebsk Raion was as follows: 61.7% for Borrelia spp., 25.8% for Anaplasma spp. (Ehrlichia spp.) and 25% for Babesia spp., mixed infections were found in 10.8% of the ticks. No tick-borne encephalitis virus genetic materials were found in the specimens. Total infection rate for ixodid ticks was 22.7%.